The Survival Outcomes of T1aN0M0 Triple-Negative Breast Cancer With Adjuvant Chemotherapy - Fu, Wen-Fen; Chen, Qing-Xia; Wang, Xiao-Xiao; Zhang, Jie; Song, Chuan-Gui (Frontiers in Oncology, 2020)
Purpose: Triple-negative breast cancer (TNBC) is a subtype with distinct heterogeneity, high invasiveness and poorer prognosis. There is a controversy about adjuvant chemotherapy (ACT) in T1aN0M0 stage. This study was carried out to assess the survival benefit of ACT to this part of patients. Methods: We identified 1099 patients with T1aN0M0 TNBC who were diagnosed from 2010 to 2016 from the Surveillance, Epidemiology, and End Results (SEER) database. Univariate and multivariable analyses were conducted to determine factors related to survival. One-to-one (1:1) propensity score matching (PSM) was applied to construct a matched sample consisting of pairs of ACT and non-ACT subjects. Breast cancer-specific survival (BCSS) and overall survival (OS) of the two groups were evaluated by Kaplan-Meier plots and Cox proportional hazard regression models. Stratified analysis according to different variables was also performed. Results: No obvious demographic or clinical characteristics difference were found between patients who had ACT and those without ACT therapy in terms of race, marital status, laterality, or radiation therapy. A higher proportion of patients who were older, had a higher histological grade tumor, and who received breast conserving surgery had adjuvant chemotherapy. The ACT group did not exhibit a better survival in BCSS or OS before propensity score matching. After PSM, the ACT and non-ACT groups consisted of 255 patients respectively, and Kaplan-Meier curves and multivariate analysis both indicated that adjuvant chemotherapy was not associated with a better survival in terms of BCSS or OS. Furthermore, we did not observe any survival advantage in any subgroup irrespective of age, race, marital status, histological grade, surgery type, or radiotherapy status. Conclusions: The study results indicated there is no strong association between ACT and better survival in T1aN0M0 TNBC. It implies that the chemotherapy decision should be made cautiously and further researches into therapeutic strategies are needed in T1aN0M0 TNBC patients.